Peran Lactoferin Susu Kuda sebagai Imunomodulator dalam Respon Imun Humoral - Nurliyani Nurliyani; Mochamad Adnan; Wayan Tunas Artama; Zuheid Noor (agriTECH, 2005)
Lactoferrin is a multifunctional defense protein, eg. as immunomodulator , which is known as glycoprotein which has 80 kDa molecullar weight. The aim of this research is to characterize of horse milk lactoferrin as immunomodulator in humoral immune response. Lactoferrin in defiled horse milk, was isolated and purified on Ion Exchange (CM Sephadex C-50) and Gel Filtration (Sephadex G-75) column. Horse milk lactoferrin is administered orally into a group of 6-8 weeks old female Balb/c mice. The dose of lactoferrin were : 0 nig (control); 0,1 mg; 0,5 mg, and 1,0 mg/mice/day in assay period of 28 day. On the r; 4 216, and 286 day, specific IgA and IgG serum of mice were detected with enzyme-linked immunosrbent assay (ELISA). The results showed that IgG and Ig,4 responses of mice that were administered with 0,5 mg or 1,0 mg horse milk lactoferrin, were higher than the control and 0,1 mg lactoferrin (P<0.05). Horse milk lactoferrin apparently induced subclass IgG1 and IgG2b response. It can be concluded that horse milk lactoferrin which has function as immunomodulator in humoral immune response